Development of Allergen-Free Cookies from Arrowroot and Taro Flours - Ramli, Nurul Kahirunnisa' Hanis; Aridi, Aida Safina (Enhanced Knowledge in Sciences and Technology, 2025)
The increasing prevalence of food allergies and sensitivities, particularly gluten-related disorder has driven demand for safe and nutritious allergen-free alternatives. This study aimed to develop allergen-free cookies using arrowroot and taro flours as substitutes for wheat flour, evaluating their physicochemical properties and sensory acceptability to determine the most preferred cookies. Allergen-free cookies made from arrowroot flour had a softer texture with hardness of 149.23 ± 25.26N and fracturability of 9.42 ± 1.00 mm, while cookies from taro flour exhibits firmer texture with hardness of 267.22 ± 12.31 N and fracturability of 8.97 ± 0.69 mm. In colour analysis, both exhibiting lighter colours with reddish and yellowish hues. Moisture content for both samples was low in the range of 6%, ensuring extended shelf life by minimizing microbial growth. Unexpectedly, the ash content was higher in cookies from arrowroot flour (1.43 ± 0.33%) than those with taro flour (0.44 ± 0.19), possibly due to errors in combustion time during ash analysis. Protein analysis showed higher protein content in cookies made from taro flour (3.24 ± 0.01%) compared to those with arrowroot flour (1.24 ± 0.03%) though the difference was not statistically significant. Sensory evaluation using a 9-point hedonic scale revealed cookies from arrowroot flour achieved a higher overall acceptability score (6.51 ± 1.690) compared to cookies from taro flour (5.86 ± 1.662). The study concluded that allergen-free cookies from arrowroot flour were the most favoured by panellists, offering desirable sensory attributes and potential nutritional benefits. The study contributes to the development of allergen-free products, catering to the growing consumer demand for safer and high nutritional value alternatives. Future research could explore ingredient modifications to further enhance texture and improve storage stability to optimize the formulation for commercial production.